(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study was to find out the comparative analysis of selected physical fitness variables among government aided and private school soccer players. To achieve the purpose of the study 80 school boys soccer players were selected static group comparison design was used as subjects from the government aided and private schools in Tirunelveli District, Tamilnadu, India during the academic year 2022– 2023. The age of subjects were ranged from 16 to 17 years. All the subjects were measured on selected physical fitness variables such as speed (60 M dash), agility (Arrow-headed Agility Test), cardio vascular endurance (12 minutes coopers run/walk test) were used to collect relevant data on the selected independent variables. The collected data from the subjects were statistically analyzed by using the statistical technique of independent-‘t’ test.. In all the cases 0.05 level of confidence was fixed as a level of confidence to test the hypotheses. It was concluded that there was a significant difference between the criterion variables.